Results of treatment and criteria of progress of respiratory organs sarkoidosis - Shvets, Kostiantyn; Ostrovskyy, Mykola (ScienceRise: Medical Science, 2018)
The aim of the work. This research work is devoted to the development of new additional criteria for the activity of inflammatory process in sarcoidosis of respiratory organs. The goal is to assess the effectiveness of performed treatment of sarcoidosis of respiratory organs by using low-cost highly-sensitive inflammatory markers. Materials and methods. The study involved 68 patients with lung sarcoidosis before and after the three-month treatment. In addition to general-clinical methods of examination, in patients with sarcoidosis we also determined the levels of TNF-α and IL-2. Results. Patients with active lung sarcoidosis had 2.61 times (p<0.05) increased level of IL-2 in bronchoalveolar lavage fluid and 9.05 times (p<0.05) increased levels in peripheral blood serum; the levels of TNF-α increased by 4.98 times (p<0.05) in bronchoalveolar lavage fluid and by 3.2 times (p<0.05) in peripheral blood serum as compared to the findings in the control group of patients. The study showed that in the group of patients, where the efficacy of the prescribed therapy was noted, the level of IL-2 decreased by 2.08 times (p<0.05) in bronchoalveolar lavage fluid and by 3.76 times (p<0.05) in peripheral blood serum, and the concentration of TNF-α decreased by 3.87 times (p<0.05) in bronchoalveolar lavage fluid and by 2.06 times in peripheral blood serum as compared to the initial indices. Conclusions. The decrease of TNF-α level in bronchoalveolar lavage fluid on the background of three-months treatment correlated (r=0.84; p<0.05) to the changes in peripheral blood serum; at the same time the decrease of TNF-α level in peripheral blood serum correlated (r=0.89; p<0.05) to the decrease of IL-2 in peripheral blood serum of patients with sarcoidosis of respiratory organs